THE ROLE OF PALLIATIVE RADIOTHERAPY IN THE TREATMENT OF METASTATIC MELANOMA - Ivanova, Maja; Stojkovski, Igor; Jovova, Solunka (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Objective: To demonstrate the role and effectiveness of palliative radiotherapy in patients with metastatic melanoma, especially in the context of combination therapy with immunotherapy and/or targeted therapy. Methodology: Four patients with metastatic melanoma, treated at the University Clinic for Radiotherapy and Oncology – Skopje are presented. All patients had a performance status (ECOG 0.1) and were treated with palliative radiotherapy due to pain and/or local progression. Different doses and techniques were used according to clinical indication combined with systemic therapy. Results: All patients showed clinical improvement after radiotherapy: pain reduction, regression of local metastases, improvement of functional status and continuation of systemic therapy without interruption. There were no significant side effects of radiotherapy. Conclusion: Palliative radiotherapy is an important tool in the multimodal approach to the management of metastatic melanoma and allows for a rapid palliative effect and potential synergism with immunotherapy and targeted therapy. Keywords:  metastatic melanoma, palliative radiotherapy, immunotherapy, targeted therapy, multimodal treatment.